PENGARUH PENDIDIKAN KEWIRAUSAHAAN DAN SELF EFFICACY TERHADAP MINAT BERWIRAUSAHA (STUDI PADA MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI TAHUN ANGKATAN 2014-2016) - -, Diajeng Galuh Chandra Kirana -; -, Harini -; -, Jonet Ariyanto Nugroho - (Pendidikan Ekonomi Bidang Keahlian Khusus Tata Niaga FKIP Universitas Sebelas Maret, 2018)
This research aims to determine (1) positive and significant effect between Entrepreneurship Education and self-efficacy on entrepreneurship interest of students of Economic Education Study Program Year 2014-2016, (2) positive and significant effect of entrepreneurship education on students? entrepreneurship interest of Economic Education Study Program Year 2014-2016, (3) positive and significant effect between self-efficacy on students? entrepreneurship interests of Economic Education Study Program Year 2014-2016.The objects of this research are 124 students of Economic Education Study Program Year 2014-2016 who enroll Entrepreneurship Education. This research uses quantitative method. The sampling data are collected using proportionate stratified random sampling technique with total sample of 124 students. The data are collected using questionnaire and documentation. Questionnaires are used to collect data about entrepreneurship education, self-efficacy and entrepreneurship interests, while documentation is used to collect data of tracer study of graduates of Economics Education, data of university-educated unemployment, and data of the number of Economics Education students who have taken Entrepreneurship Education subject. The data are analyzed using multiple regression analysis.The result of this research are: (1) There is a positive and significant effect between entrepreneurship education and self-efficacy to entrepreneurship interest of students of Economic Education Program Year 2014-2016 which is shown by the total of Fcount is bigger than Ftable, that is 12,569 > 3.07. (2) There is a positive and significant effect between entrepreneurship education on students? entrepreneurship interest of Economic Education Study Program Year 2014-2016 which is shown by the total of tcount of entrepreneurship education variable is 4,372> ttable that is 1,979 and total sig. 0,000 <0.05. (3) There is positive and significant effect between self-efficacy on students? entrepreneurship interest of Economic Education Study Program Year 2014-2016 which shown by tcount of self-efficacy, that is 2.031> ttable that is 1,979 and total sig. 0,000 <0.05.